2021
DOI: 10.21203/rs.3.rs-907818/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Expression Profiles and Clinical Significance of PKM2 and Notch1 in Colorectal Cancer

Abstract: Background Studies have shown that pyruvate kinase M2 (PKM2) and Notch1 are highly expressed in colorectal cancer (CRC) tissues and have a certain relationship with disease occurrence and development. The expression levels of PKM2 and Notch1 are also related to the effect of chemotherapy and radiotherapy, which seriously influence the prognosis of CRC patients. Thus, both PKM2 and Notch1 have been identified as key targets of CRC treatment and research. However, correlations between PKM2 and Notch1 have not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…NRCAM, a gene encoding a neuronal cell adhesion molecule, promotes CRC through the beta-catenin/LEF-1 pathway [41]. It has also been demonstrated that NRCAM, LRFN4, and PHGDH are upregulated in CRC tissues compared to normal samples around the tumor and serve as predictors of poor clinical outcomes in advanced CRC patients [42][43][44]. Tumor genome sequencing data have indicated that GRM1 is one of the pivotal driving genes for CRC stage II progression [45].…”
Section: Discussionmentioning
confidence: 99%
“…NRCAM, a gene encoding a neuronal cell adhesion molecule, promotes CRC through the beta-catenin/LEF-1 pathway [41]. It has also been demonstrated that NRCAM, LRFN4, and PHGDH are upregulated in CRC tissues compared to normal samples around the tumor and serve as predictors of poor clinical outcomes in advanced CRC patients [42][43][44]. Tumor genome sequencing data have indicated that GRM1 is one of the pivotal driving genes for CRC stage II progression [45].…”
Section: Discussionmentioning
confidence: 99%